2008
DOI: 10.1136/ard.2008.094904
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept therapy in rheumatoid arthritis and the risk of malignancies: a systematic review and individual patient data meta-analysis of randomised controlled trials

Abstract: In this analysis, the point estimate of malignancy risk was higher in etanercept-treated patients, although the results were not statistically significant. The approach of obtaining individual patient data of RCT in cooperation with trial sponsors allowed important insights into the methodological advantages and challenges of sparse adverse event data meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 34 publications
2
81
2
5
Order By: Relevance
“…TNF plays an important role in tumour growth control and host defence, and biologic therapy targeting TNF determines an important immunomodulation, raising thus the concern of a possible increased risk of malignancies in patients treated with anti-TNF antibodies. Regarding short-term cancer risk, meta-analysis of clinical trials suggested an increased risk of cancer development (Bongartz et al, 2006, Leombruno et al, 2009, Bongartz et al, 2009), but observational studies did not confirm these results. Randomized controlled trials provide balanced groups for analysis and a well-selected study population but, on the other hand, considering that the time interval from the onset of cancer until its clinical manifestation is counted in years and not in months, any long-term effect of therapy cannot be correctly estimated using data from clinical trials.…”
Section: Anti-tnf Agentsmentioning
confidence: 76%
“…TNF plays an important role in tumour growth control and host defence, and biologic therapy targeting TNF determines an important immunomodulation, raising thus the concern of a possible increased risk of malignancies in patients treated with anti-TNF antibodies. Regarding short-term cancer risk, meta-analysis of clinical trials suggested an increased risk of cancer development (Bongartz et al, 2006, Leombruno et al, 2009, Bongartz et al, 2009), but observational studies did not confirm these results. Randomized controlled trials provide balanced groups for analysis and a well-selected study population but, on the other hand, considering that the time interval from the onset of cancer until its clinical manifestation is counted in years and not in months, any long-term effect of therapy cannot be correctly estimated using data from clinical trials.…”
Section: Anti-tnf Agentsmentioning
confidence: 76%
“…Studies like those by Demirkaya et al (6), in which they find that lymphocytes from children with JIA treated with anti-TNF agents were more sensitive to genotoxic stress and less efficient at DNA repair than were cells from the same patients prior to the initiation of anti-TNF therapy, may point to important pathways and potential tests for clinical use. If a subset of patients with JIA or RA exhibit increased spontaneous levels of DNA damage or increased genotoxicity when treated with anti-TNF agents, for example, then these patients may represent a subset of susceptible patients who would benefit from close followup to detect the development of malignancies, or who should be treated with other drugs not associated with malignancy, such as agents that block T cell costimulation.…”
Section: To the Editorsmentioning
confidence: 91%
“…Some studies have suggested that the risk of malignancy is lower for patients with RA treated with etanercept than with the other medications. A recent meta-analysis of 9 trials including 3,316 patients, 2,244 of whom received etanercept, did not show a statistically significant increase in cancer development in those receiving etanercept (30). Close analysis of the French registry subjects also revealed that although patients receiving adalimumab or infliximab had an SIR of 4.1 or 3.6, respectively, for cancer development, the SIR for patients receiving etanercept or methotrexate was only 0.9 (20).…”
Section: Anti-tnf Therapy and Cancermentioning
confidence: 99%